Improved electron–hole separation and migration in anatase TiO2 nanorod/reduced graphene oxide composites and their influence on photocatalytic performance. Issue 13 (21st March 2017) - Žerjav, Gregor; Arshad, Muhammad Shahid; Djinović, Petar; Junkar, Ita; Kovač, Janez; Zavašnik, Janez; Pintar, Albin
Abstract : A graphical illustration of TNR + rGO composites and a possible mechanism for improved charge migration. Abstract : The as-synthesized TiO2 nanorods a-TNR (amorphous TiO2 layer covering the crystalline anatase TiO2 core) and TNR (fully crystalline anatase TiO2 ) were decorated with reduced graphene oxide (rGO) to synthesize two series of TiO2 + rGO composites with different nominal loadings of GO (from 4 to 20 wt%). The structural, surface and electronic properties of the obtained TiO2 + rGO composites were analyzed and correlated to their performance in the photocatalytic oxidation of aqueous bisphenol A solution. X-ray photoelectron spectroscopy (XPS) analyses revealed that charge separation in TiO2 + rGO composites is improved due to the perfect matching of TiO2 and rGO valence band maxima (VBM). Cyclic voltammetry (CV) experiments revealed that the peak-to-peak separations (Δ E p ) are the lowest and the oxidation current densities are the highest for composites with a nominal 10 wt% GO content, meaning that it is much easier for the charge carriers to percolate through the solid, resulting in improved charge migration. Due to the high charge carrier mobility in rGO and perfect VBM matching between TiO2 and rGO, the electron–hole recombination in composites was suppressed, resulting in more electrons and holes being able to participate in the photocatalytic reaction. rGO amounts above 10 wt% decreased the photocatalytic activity; thus, it is critical to optimize its amount in the TiO2 + rGO composites for achieving the highest photocatalytic activity. BPA degradation rates correlated completely with the results of the CV measurements, which directly evidenced improved charge separation and migration as the crucial parameters governing photocatalysis.